Physical activity, diet, and social determinants of health associate with health related quality of life and fibrosis in MASLD - Blake C. Czapla; Anushka Dalvi; Jingyi Hu; Isabel J. Moran; Karn Wijarnpreecha; Vincent L. Chen (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is a leading cause of end-stage liver disease. MASLD and liver fibrosis are associated with cardiometabolic risk factors and health-related quality of life (HRQOL) while being affected by dietary/exercise patterns and social determinants of health (SDOH). However, previous studies have not assessed in conjunction exercise, diet, SDOH, and HRQOL in patients with MASLD. This was a cross-sectional study of patients with MASLD seen in hepatology clinic at University of Michigan. Participants completed validated surveys on HRQOL, diet, and physical activity, and a subset also underwent vibration controlled transient elastography (VCTE). The primary outcomes were HRQOL (measured by Short Form-8) and cirrhosis, and predictors were physical activity, dietary patterns, cardiometabolic comorbidities, and social determinants of health. The primary analysis included 304 patients, with median body mass index 32.4 kg/m2 and prevalence of type 2 diabetes, hypertension, and dyslipidemia 38%, 45%, and 42%, respectively (Table 1). The majority of the participants had a FIB-4 score of less than 1.3 and LSM of less than 8 (Table 1). HRQOL was lower with higher BMI, type 2 diabetes, hypertension, and increased liver fibrosis, and higher in people with adequate fruit intake. Neighborhood-level SDOH were also associated with HRQOL. Factors associated with cirrhosis or higher liver stiffness measurement by VCTE included body mass index, diabetes, and living in an impoverished neighborhood, while increased vegetable intake and exercise were associated with lower prevalence of cirrhosis/fibrosis. In multivariable models including demographic and cardiometabolic factors, dietary patterns and SDOH were independently associated with HRQOL and cirrhosis. Cardiometabolic risk factors, physical activity, diet, and social determinants of health are associated with HRQOL and liver fibrosis.